Assessing heritability of biochemical limitations in photosynthesis can help elucidate new targets for improvement. (20th April 2022) - Acevedo‐Siaca, Liana G.; Long, Stephen P.
Abstract: Understanding heritability has historically been critical to the incorporation of traits of interest into plant breeding programmes for improvement. In our previous study, we assessed the heritability of several photosynthetic traits in indica rice, including biochemical limitations of photosynthesis. Here, we discuss that even without directly evaluating sink limitation, there is still great value in this study for understanding how photosynthetic traits in rice could be incorporated into a breeding programme and which traits could be given priority. Additionally, we assert that limitation by J max will likely be more relevant than TPU limitation in the immediate future and could be a valuable factor for selection. However, we agree with Fabre and Dingkuhn (2022, https://doi.org/10.1111/pbr.13000 ) that sink limitation should be further examined within the context of plant improvement in the future.